An Efficient Broadcast Encryption Supporting Designation and Revocation Mechanisms. Issue 3 (1st May 2019) - Zhu, Yan; Yu, Ruyun; Chen, E; Huang, Dijiang
Abstract : In this paper our objective is to explore approaches of secure group‐oriented communication with designation and revocation mechanisms simultaneously. We present a new scheme of Revocation‐based broadcast encryption (RBBE) which is designed on Dan Boneh et al. 's scheme with the designation mechanism proposed in 2005. We combine two above‐mentioned schemes into a new cryptosystem, called Dual‐mode broadcast encryption (DMBE). Based on these work, we reach the following conclusions. We use the DMBE scheme as an example to show that it is feasible to construct a broadcast encryption scheme that supports designation and revocation mechanisms simultaneously. The cryptosystem with dual modes is more e.cient than that with single mode over computational costs, and the performance is improved to at most O(⌈N/2⌉), where N is the total number of users in the system. We prove completely that both the RBBE scheme and the DMBE scheme are semantically secure against chosen plaintext attack with full collusion under the decisional bilinear Di.e‐Hellman exponent assumption.